The expression for (r-s)(x) is found by subtracting s from r. That difference is
. The expression for (r+s)(x) is found by adding them, which is
. Now we are told to evaluate (r*s)(x) which means they want us to multiply those and state the "new" expression that results.
. There you go!
54554/99999. I think I am right but sorry if I am wrong.
Answer: 9
Step-by-step explanation:
Use Pythagorean's Theorem for a right triangle.
Answer:
here is an an example
Step-by-step explanation:
Let x = the width of the rectangle
P = 2l + 2w
2(40) + 2x ≤ 150
80 + 2x ≤ 150
2x ≤ 70
x ≤ 35 cm